1986
DOI: 10.1115/1.3269309
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Method of Gear Noise Considering the Influence of the Tooth Flank Finishing Method

Abstract: Simple and accurate prediction methods of gear unit noise have been desired. This paper offers a new prediction equation for spur and helical gears under speed reduction service. A semi-empirical equation was developed by means of the addition of a dynamics term to Kato’s equation which represented the overall noise level by using gear’s specification data. As the proposed method takes into account the gear error characteristics in the vibration analysis of gear pairs, it can calculate the noise levels conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In case the rotary speed is constant, the change of radiated noise and load torque conforms to the conclusion that reducer noise and 20logW are in proportion drawn by Niemann and Kato 3 namely where N T is the load coefficient of proportion, T is the load torque, L ( T ) is the sound pressure level when load torque is T.…”
Section: Influence Of Operating Condition On Noise Radiation Under Hesupporting
confidence: 73%
See 2 more Smart Citations
“…In case the rotary speed is constant, the change of radiated noise and load torque conforms to the conclusion that reducer noise and 20logW are in proportion drawn by Niemann and Kato 3 namely where N T is the load coefficient of proportion, T is the load torque, L ( T ) is the sound pressure level when load torque is T.…”
Section: Influence Of Operating Condition On Noise Radiation Under Hesupporting
confidence: 73%
“…Since Kato formula fails to embody natural frequency of the transmission system, the changing trend of the result dependent on linear speed of gear addendum is smooth, and the noise of reducer is increased with the increase of rotary speed. 3 Calculation by FEM/BEM is not only to take dynamic characteristics of the gear reducer into consideration, therefore, the noise curve is fluctuant to a certain extent. In case of 750 r/min, since the 6-times gear frequency component in the excitation is closer to the first-order natural frequency of the transmission system, the transmission system generates larger vibration, and making noise radiation curves a and b deviate from d 1 =7 dB; in case of 2100 r/min, since 2-times component (1398 Hz) of meshing force is closer to the second-order natural frequency of gearbox, it results in larger vibration in gearbox making noise radiation deviate from d 2 =5 dB, if the two resonance positions are not considered, the deviation of two curves in other positions is within 3dB, accordingly, and it is observed that results of simulation calculation and results of calculation by Kato are consistent.…”
Section: Influence Of Operating Condition On Noise Radiation Under Hementioning
confidence: 99%
See 1 more Smart Citation
“…By adding a dynamic term to the Kato [17] equation, which determines the general noise level using the gear's specification data, a semi-empirical equation has been developed that takes into account the effect of the tooth side surface finishing method. It was stated that the data obtained from the test gears through the experiments were in accordance with the data obtained from the equation with 5 dB tolerance [18]. KISSsoft commercial software calculates the noise level in gear wheels based on the Masuda equation.…”
Section: Masuda Gear Noise Equationmentioning
confidence: 73%
“…In the early stages of research, empirical formulas for the estimation of the noise intensity of a gear pair were obtained based on many experiments [11]- [13]. However, these acoustic estimates may not be suitable for other gearboxes, as the radiated noise depends strongly on the shape of the housing.…”
Section: Introductionmentioning
confidence: 99%